Comparação entre dois modelos de treinamento sobre o gasto energético de repouso e a composição corporal de adolescentes com obesidade - de Oliveira, Bruno Affonso Parenti; Rossi, Fabrício Eduardo [UNESP]; Buonani, Camila [UNESP]; Diniz, Tiego Aparecido [UNESP]; Monteiro, Paula Alves [UNESP]; Antunes, Bárbara de Mello [UNESP]; Fernandes, Rômulo Araújo [UNESP]; Freitas Júnior, Ismael Forte [UNESP] (FapUNIFESP (SciELO), 2016)
Different types of physical activity programs have been used with the purpose of improving body composition and increasing resting energy expenditure (REE) in obese adolescents. The aim of the present study was to compare the effects of two training models on REE and body composition in this population. The study included 20 obese male adolescents, who were randomly assigned to follow two training models: strength training (n=8, age=13,4±1.0) and functional training (n=12, age= 13.0±1.1). Body composition variables were estimated by dual-energy X-ray absorptiometry. REE was assessed by indirect calorimetry using the QUARK-PFT equipment (COSMED, Rome, Italy). The training protocol consisted of 30 minutes of aerobic training followed by 30 minutes of strength training (ST) or functional training (FT), both with a duration of 20 weeks. There were no significant differences between the two training models with regard to body composition (fat mass, FT= -7.6±5.5% vs. ST= -8.9±6.2%; p=0.620), (lean body mass, FT= 9.0±5.3% vs. ST= 6.8±6.7%; p=0.431) and to REE (FT= 19.6±15.3% vs. ST= 10.7±24.5%; p=0.331). Moreover, lean body mass (p=0.01) and fat mass (0.01) had an influence on REE. No differences were observed between the two training models, but both were effective in improving body composition and increasing REE in obese adolescents. Furthermore, the present study showed the importance of systematic physical training, since lean body mass and fat mass contributed to the increase in REE after the training period.
Comparison between two models of training with regard to resting energy expenditure and body composition in obese adolescents
Keywords: Adolescents; Body composition; Obesity; Training